Male sterility in dry beans - Singh, S.P.; White, J.W.; Gutiérrez, J.A. (1980)
Thirteen male sterile plants were identified in a yield trial of bean germplasm accession G08063 grown at CIAT-Palmira in 1977. Line G08063 is indeterminate, type III with postrate growth; it is relatively early and produces small white seeds. A fertility score (less than 1.3 sterile, 1.3-2.5 partially sterile, and more than 2.5 fertile) and the amount of pod set were used to validate the male sterility of the 13 plants, and to determine their progeny fertility. Selected male sterile plants were crossed with several fertile parents; data on the F1 are presented. (CIAT)